The Effect of Income and Inflation on Household Consumption Expenditures in Indonesia (A Case Study of 34 Provinces) - Izza Muzaiyana; Hakim Muttaqim; Azka Rizkina (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze the effect of income and inflation on household consumption expenditure in 34 provinces in Indonesia. The main issue raised is the fluctuation in household consumption, which does not always move in line with changes in income and inflation, even though these two variables are generally considered to play an important role in determining the level of community welfare. This study uses secondary data obtained from the Central Statistics Agency (BPS) for the period 2016–2024. The method applied is a quantitative approach with panel data regression analysis to see the relationship between variables more comprehensively. The best model was determined through a series of model selection tests, namely the Chow, Hausman, and Lagrange Multiplier tests. Based on the results of these three tests, the Common Effect model was selected as the most appropriate model to describe the relationship between income, inflation, and household consumption. The analysis results show that income and inflation have no significant effect, either partially or simultaneously, on household consumption expenditure. In addition, the low coefficient of determination indicates that most of the variation in consumption is influenced by factors other than those included in this research model. These findings indicate the need for economic policies that focus more on increasing purchasing power and controlling prices in order to maintain the stability of household consumption in Indonesia.